Alternative Worlds: the emergence of Theatre for Young Audiences from the conflict in Northern Ireland. - Tom Maguire (Strenae)
This essay traces the development of an identifiable sector of Theatre for Young Audiences in Northern Ireland during the ethno-religious violent conflict known as The Troubles from 1968 to 1998. During that period, children were regarded as a largely homogeneous group within legislative and policy frameworks that were concerned primarily with the impact of that conflict on children. This period saw the emergence of a theatre specifically for children, without any over-arching sense of a sector. Following the signing of the Belfast Agreement of 1998, the broader turn to a rights-based culture amplified the impact of the United Nations’ Convention on the Rights of the Child (1989) within government policy and the growth of a culture that promoted, more broadly, the child as an autonomous human being. In parallel to this turn, a recognizable children’s theatre sector developed to create spaces locally for children to attend performances, and performances which engage with the aesthetics of Theatre for Young Audiences internationally through collaboration and partnerships.